Biochar from Kapuk Randu (Ceiba pentandra) Seeds for Adsorption of Remazol Blue Dye in Wastewater - Napitupulu*, Mery; Walanda, Daud Karel; Nakazawa, Koyomi; Poba, Detris; Tiwow, Vanny M A; Nurmayanti, Yuli; Rahma, Sri (Jurnal IPA & Pembelajaran IPA, 2025)
The use of synthetic dyes such as remazol by textile companies can harm the environment because they are toxic, long-lasting, and hard to break down. This study aims to find out how well biochar made from randu kapuk seeds can absorb colors in water by determining the best weight, contact time, and pH level. The study's findings indicate that the moisture content of biochar made from randu kapuk seeds at temperatures of 400C, 450C, and 500C is 5.7%, 5.1%, and 4.3%, respectively. The ash concentration at temperatures of 400, 450, and 500 was 7.7%, 6.8%, and 6.3%, respectively. The best amount of biochar tested was 100 mg, which could absorb 25 mg of remazol Blue, giving it an adsorption capacity of 1.65 mg/g. The best time for biochar made from kapuk seeds to absorb remazol Blue was 30 minutes, with an absorption ability of 1.59 mg/g. The optimal pH for the adsorption of remazol Blue was 4, with a capacity of 5.39 mg/g. The results showed that biochar made from kapuk seeds was excellent at soaking up substances and followed certain patterns that suggest it works through a single layer of chemical bonding. This study highlights how effective biochar made from kapuk seeds is as a safe and eco-friendly material for cleaning dye-polluted water, which helps promote sustainable water management in line with SDG 6: clean water and sanitation